2016
DOI: 10.1080/17512433.2016.1245142
|View full text |Cite
|
Sign up to set email alerts
|

Early drug development: assessment of proarrhythmic risk and cardiovascular safety

Abstract: Introduction: hERG assays and thorough ECG trials have been mandated since 2005 to evaluate the QT interval and potential proarrhythmic risk of new chemical entities. The high cost of these studies and the shortcomings inherent in these binary and limited approaches to drug evaluation have prompted regulators to search for more cost effective and mechanistic paradigms to assess drug liability as exemplified by the CiPA initiative and the exposure response ICH E14(R3) guidance document. Areas covered: This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Toxicological structure alerts (toxicophores) need to be avoided in the development of any drug that is to be dosed chronically, particularly in elderly or frail patients who are likely to present with comorbidities, including reduced renal and liver function, or in patients who have previously been treated with multiple lines of anticancer therapy and are therefore likely to have a poor performance status. Avoidance of drugs that have high risk of hERG voltage-gated potassium channel blockade, which is associated with potentially fatal cardiotoxicity, is a special case in point 100 . Other pharmacological features associated with on-target and off-target toxicities also need to be avoided, particularly the generation of reactive metabolites that can cause carcinogenicity and nonspecific cytotoxicity.…”
Section: Drug Propertiesmentioning
confidence: 99%
“…Toxicological structure alerts (toxicophores) need to be avoided in the development of any drug that is to be dosed chronically, particularly in elderly or frail patients who are likely to present with comorbidities, including reduced renal and liver function, or in patients who have previously been treated with multiple lines of anticancer therapy and are therefore likely to have a poor performance status. Avoidance of drugs that have high risk of hERG voltage-gated potassium channel blockade, which is associated with potentially fatal cardiotoxicity, is a special case in point 100 . Other pharmacological features associated with on-target and off-target toxicities also need to be avoided, particularly the generation of reactive metabolites that can cause carcinogenicity and nonspecific cytotoxicity.…”
Section: Drug Propertiesmentioning
confidence: 99%
“…The effect of drugs on cardiac repolarization-through assessment of the QT interval of the electrocardiogram (ECG)-is an important tool in the assessment of the propensity of novel medical products to induce arrhythmias, which has been a major cause of drug withdrawals from the market or clinical development. [1][2][3][4] Clinical and pharmacological studies have indicated that the vulnerability to induced arrhythmias varies throughout the day. 5,6 Regulation of cardiac function by diurnal factors enables efficient coupling of physiological response to anticipated environmental demand.…”
mentioning
confidence: 99%
“…Although this basic model is already useful, it can be extended in several ways to make it more powerful. First, the model can be generalised to predict overall cardiovascular risk and not just QT interval prolongation (Lester and Olbertz, 2016); for example, by using data from the Comprehensive in vitro Proarrhythmia Assay (CIPA) or haemodynamic/ECG data from an in vivo model to predict broader arrhythmia potential (Sager et al, 2014). However, with more predictor variables and a fixed number of compounds (observations), there is a risk that noise will be mistaken for signal (over-fitting), leading to better predictions for the current data, but worse predictions on future data.…”
Section: Discussionmentioning
confidence: 99%